Initial conditions for accurate N-body simulations of massive neutrino cosmologies. Issue 3 (23rd December 2016) - Zennaro, M.; Bel, J.; Villaescusa-Navarro, F.; Carbone, C.; Sefusatti, E.; Guzzo, L.
Abstract: The set-up of the initial conditions in cosmological N -body simulations is usually implemented by rescaling the desired low-redshift linear power spectrum to the required starting redshift consistently with the Newtonian evolution of the simulation. The implementation of this practical solution requires more care in the context of massive neutrino cosmologies, mainly because of the non-trivial scale-dependence of the linear growth that characterizes these models. In this work, we consider a simple two-fluid, Newtonian approximation for cold dark matter and massive neutrinos perturbations that can reproduce the cold matter linear evolution predicted by Boltzmann codes such as camb or class with a 0.1 per cent accuracy or below for all redshift relevant to non-linear structure formation. We use this description, in the first place, to quantify the systematic errors induced by several approximations often assumed in numerical simulations, including the typical set-up of the initial conditions for massive neutrino cosmologies adopted in previous works. We then take advantage of the flexibility of this approach to rescale the late-time linear power spectra to the simulation initial redshift, in order to be as consistent as possible with the dynamics of the N -body code and the approximations it assumes. We implement our method in a public code (REPS rescaled power spectra for initial conditions with massive neutrinos https://github.com/matteozennaro/reps ) providing the initial displacements and velocities for cold dark matter and neutrino particles that will allow accurate, i.e. 1 per cent level, numerical simulations for this cosmological scenario.